Genotoxicological Evaluation of NUTRALYS Pea Protein Isolate. (3rd June 2013) - Aouatif, Chentouf; Looten, Ph.; Parvathi, M. V. S.; Raja Ganesh, S.; Paranthaman, V.
Abstract : NUTRALYS Pea Protein Isolate, a protein supplement, is a high-quality source of protein which is primarily emulsifying functional protein. We evaluated the genotoxic potential of NUTRALYS isolated from dry yellow pea, using three established genotoxicity tests (AMES test in vitro chromosomal aberration test, and in vivo micronucleus test) employing OECD guidelines under GLP conditions. In the bacterial reverse mutation test, NUTRALYS did not show positive responses in strains detecting point and frame shift mutations. In the chromosomal aberration test, NUTRALYS did not induce chromosome aberrations in the presence and absence of metabolic activation. In the bone marrow micronucleus test, NUTRALYS did not induce significant increases of micronucleated immature (polychromatic) erythrocytes in bone marrow of test animals.